Effects of the auxin-dependent degradation of the cohesin and condensin complexes on the repair of distant DNA double-strand breaks in mouse embryonic stem cells - A. V. Smirnov; A. S. Ryzhkova; A. M. Yunusova (Вавиловский журнал генетики и селекции)
The SMC protein family, including cohesin and condensin I/II, plays a pivotal role in maintaining the topological structure of chromosomes and influences many cellular processes, notably the repair of double-stranded DNA breaks (DSBs). The cohesin complex impacts DSB repair by spreading γH2AX signal and containing DNA ends in close proximity by loop extrusion. Cohesin supports DNA stability by sister chromatid cohesion during the S/G2 phase, which limits DNA end mobility. Cohesin knockdown was recently shown to stimulate frequencies of genomic deletions produced by distant paired DSBs, but does not affect DNA repair of a single or close DSBs. We examined how auxin-inducible protein degradation of Rad21 (cohesin) or Smc2 (condensins I+II) changes the frequencies of rearrangements between paired distant DSBs in mouse embryonic stem cells (mESCs). We used Cas9 RNP nucleofection to generate deletions and inversions with high efficiency without additional selection. We determined optimal Neon settings and deletion appearance timings. Two strategies for auxin addition were tested (4 independent experiments in total). We examined deletion/inversion frequencies for two regions spanning 3.5 and 3.9 kbp in size. Contrary to expectations, in our setting, Rad21 depletion did not increase deletion/inversion frequencies, not even for the region with an active Ctcf boundary. We actually observed a 12 % decrease in deletions (but not inversions). At the same time, double condensin depletion (Smc2 degron line) demonstrated high biological variability between experiments, complicating the analysis, and requires additional examination in the future. TIDE analysis revealed that editing frequency was consistent (30–50 %) for most experiments with a minor decrease after auxin addition. In the end, we discuss the Neon/ddPCR method for deletion generation and detection in mESCs.